Peran Literasi Keuangan dan Modal Sosial terhadap Kinerja dan Keberlanjutan Usaha Pelaku UMKM - Masdiantini, Putu Riesty; Devi, Sunitha; Kusyanda, Made Riki Ponga (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This research aims to obtain empirical evidence regarding the influence of financial literacy and social capital on the performance and business sustainability of MSMEs in Buleleng Regency. The population in this research is all MSMEs in Buleleng Regency that are registered in the Dinas Perdagangan, Perindustrian, and Koperasi, UKM of Buleleng Regency until 2022. The determination of the sample size was carried out using non-probability sampling techniques to obtain a sample of 115 respondents. This research is a quantitative approach with Structural Equation Modeling (SEM) analysis analyzed using SEM SmartPLS 3.0. The research results show that financial literacy has a positive significant effect on the business performance of MSMEs; financial literacy has a positive significant effect on the business sustainability of MSMEs; social capital has a positive significant effect on the business performance of MSMEs; and social capital has a positive significant effect on the business sustainability of MSMEs.